Properties of apyrase and inorganic pyrophosphatase in Streptomyces aureofaciens - Curdová, E; Jechová, V; Hostálek, Z (Folia microbiologica, 1982)
Apyrase (ATP-diphosphohydrolase, EC 3.6.1.5) and inorganic pyrophosphatase (EC 3.6.1.1) were partially purified from S. aureofaciens RIA 57 and characterized. Apyrase degrades, in addition to ATP, other nucleoside triphosphates and nucleoside diphosphates, diphosphate, thiamine diphosphate, phosphoenolpyruvate and oligophosphates of chain length n less than 90. The apyrase activity was detected in the membrane and supernatant fractions. Its properties (substrate specificity. effect of inhibitors, pH optimum and effect of Mg2+ ions) were similar in both fractions except for the effect of oligomycin that inhibited only the membrane fraction. Pyrophosphatase exhibited a strict substrate specificity, substrates other than diphosphate being degraded relatively slowly. Of other enzymes exhibiting the phosphatase activity acid phosphatase (EC 3.1.3.2) and alkaline phosphatase (EC 3.1.3.1), trimetaphosphatase (EC 3.6.1.2) and exopolyphosphatase (EC 3.6.1.11) degrading oligophosphatase of chain length n = 15, 40 and 60, were detected.
Keywords: apyrasa; hořčík; nukleotidy; Pyrophosphatases; fosfatasy; substrátová specifita; Membranes; koncentrace vodíkových iontů; Streptomyces; Apyrase; pyrofosfatasy; membrány; Phosphoric Monoester Hydrolases; Hydrogen-Ion Concentration; adenosintrifosfát; Magnesium; Substrate Specificity; Nucleotides; Adenosine Triphosphate